Effects of humic acid modified oyster shell addition on lignocellulose degradation and nitrogen transformation during digestate composting. (June 2021) - Lu, Mingyi; Shi, Xiaoshuang; Feng, Quan; Li, Xu; Lian, Shujuan; Zhang, Mengdan; Guo, Rongbo
Graphical abstract: Highlights: Humic acid modified oyster shell was applied in the digestate composting. The addition of modified oyster shell enhanced the lignocellulose degradation. Modified oyster shell reduced NO3 − generation by inhibiting nitrifying bacteria. The N2 O emission was reduced by 59.63% with modified oyster shell added. Addition of modified oyster shell affected the diversity of bacterial community. Abstract: The aim of this work was to investigate the performance of a novel humic acid modified oyster shell (MOS) bulking agent on the digestate composting. MOS was prepared by immobilizing humic acid onto oyster shell using solid phase grafting method, and then applied to the composting process. Results showed more obvious degradation of lignocellulose was observed in the MOS treatment, which was probably due to the high relative abundance of Actinobacteria . Moreover, the addition of MOS could significantly preserve NH4 + and reduce the NO3 − generation with the decreasing abundance of ammonia-oxidizing bacteria and archaea. Besides, adding MOS reduced the N2 O emission by 59.63% compared with the control. After composting, excitation-emission matrix fluorescence spectra demonstrated that the humification degree as well as compost maturity was enhanced with MOS added.